Analysis of the Predictors of Unemployment of Venezuelan Migrants in the city of Barranquilla through a Logistic Regression Model - Javier Ramirez; Jesus García; Evaristo Navarro; William Niebles (Migration Letters, 2023)
This research sought to analyze the predictors of unemployment of Venezuelan migrants in Barranquilla through a logistic regression model. A correlational research is presented, in which a sample of 931 Venezuelan migrants in Barranquilla is taken, to whom an instrument aimed at sociodemographic elements linked to living conditions and employment status is applied. Regarding the statistical treatment, a logistic regression analysis is applied, which sought to determine which elements are predictors of unemployment of the migrant population. These findings show as outstanding elements: being active within the informal economy, performing economic activities recognized as trades and having owned a business in Venezuela. It is concluded that there is a condition of vulnerability in Venezuelan migrants as a result of being inserted in the informal sector, being the predictor factors those established in the regression model, with a level of significance.